Neurological symptoms and disorders following electrical injury: A register-based matched cohort study. - Kent J Nielsen; Ole Carstensen; Anette Kærgaard; Jesper Medom Vestergaard; Karin Biering (PLoS ONE)
Introduction Electric shocks may have neurological consequences for the victims. Although the literature on the neurological consequences of electric shocks is limited by retrospective designs, case studies and studies of selected patient groups, previous research provides some evidence of a link between electric shocks, and diseases and symptoms of the central nervous system (CNS)(e.g. epilepsy, migraine and vertigo) and the peripheral nervous system (PNS)(e.g. loss of sensation, neuropathy and muscle weakness). This study aims to employ a register-based, matched cohort study, to investigate whether individuals demonstrate a greater risk of neurological diseases and symptoms of the CNS or PNS in the years following an electrical injury. Materials and methods We identified 14,112 electrical injuries over a period of 19 years in two Danish registries, and matched these with three different groups of persons in a prospective matched cohort study: (1) patients with dislocation/sprain injuries, (2) patients with eye injuries and (3) persons employed in the same occupation. Year of injury, sex and age were used as matching variables. The outcomes we identified comprised neurological disorders and central or peripheral nervous system symptoms that covered a range of diagnoses in the Danish National Patient Register. The associations were analysed using conditional logistic regression for a range of time periods (six months to five years) and conditional Cox regression for analyses of the complete follow-up period (up to 20 years). Results For victims of electric shock, the CNS sequelae we identified included an increased risk of epilepsy, convulsions, abnormal involuntary movements, headache, migraine and vertigo. We also identified an uncertain, increased risk of spinal muscular atrophy and dystonia, whereas we identified no increased risk of Parkinson's disease, essential tremor, multiple sclerosis or other degenerative diseases of the nervous system. For victims of electric shock, the PNS sequelae we identified included an increased risk of disturbances of skin sensation, mononeuropathy in the arm or leg and nerve root and plexus disorders. We also identified an uncertain, increased risk of facial nerve disorders, other mononeuropathy, and polyneuropathy. Conclusion Our results confirm that electrical injuries increase the risk of several neurological diseases and symptoms of the CNS or PNS in the years following the injury. Most often the diseases and symptoms are diagnosed within the first six months of the injury, but delayed onset of up to 5 years cannot be ruled out for some symptoms and diagnoses. Some of the conditions were rare in our population, which limited our ability to identify associations, and this warrants cautious interpretation. Therefore, further studies are needed to confirm our findings, as are studies that examine the mechanisms underlying these associations.